2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037840
|View full text |Cite
|
Sign up to set email alerts
|

Continuous bladder volume monitoring system for wearable applications

Abstract: In this research, we propose a bladder volume monitoring system that can be effectively applied for various voiding dysfunctions. Whereas conventional systems lack consecutive measurements, the proposed system can continuously monitor a user's status even during unconscious sleep. For the convenience, we design a simple and comfortable waist-belt-type device by using the body impedance analysis (BIA) technique. To support various measurement scenarios, we develop applications by connecting the device to a smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The 3D surface model was then scaled by 0.516 to allow for rapid prototyping (3D printing) on a Ultimaker 2 Extended+ (Ultimaker, Geldermalsen, Netherlands). This scale makes the model suitable for use in urinary applications for children using electrical impedance (Shin et al, 2017) and as a near-half scale model of an adult male.…”
Section: Design Of the Outer Wallmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3D surface model was then scaled by 0.516 to allow for rapid prototyping (3D printing) on a Ultimaker 2 Extended+ (Ultimaker, Geldermalsen, Netherlands). This scale makes the model suitable for use in urinary applications for children using electrical impedance (Shin et al, 2017) and as a near-half scale model of an adult male.…”
Section: Design Of the Outer Wallmentioning
confidence: 99%
“…Bladder volume monitoring using electrical impedance (EI) techniques has been studied in simulation , with simplified tank-based measurements (He et al, 2012;, on animals (Denniston and Baker, 1975;Zariffa et al, 2016), and on humans (Kim et al, 1998;Leonhardt et al, 2011;Liao and Jaw, 2011;Zariffa et al, 2016, Shin, et al, 2017. Human studies have shown strong correlation of bladder volume with the processed EI data (Leonhardt et al, 2011;Li et al, 2016), highlighting the feasibility of EI to continuously monitor bladder volume in clinical situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies on wearable non-invasive measuring equipment have been conducted using near-infrared spectroscopy [ 12 , 13 ], bioimpedance [ 14 , 15 ], and ultrasound [ 16 , 17 , 18 , 19 , 20 ]. Near-infrared spectroscopy and bioimpedance techniques assume that the optical and electrical properties of pelvic organs are constant and that variations in measurements result from changing the amount of urine in the bladder.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodes used for EI measurement can be woven into underwears (textrode), thereby overcoming the limitations of the size faced by existing ultrasound devices. The miniaturization of EI measurement devices is crucial for implementing them as a clinically applicable urine volume estimation tool, and several studies have developed wearable sensors [6], [7]. However, a tradeoff exists between portability, wearability, and estimation accuracy.…”
Section: Introductionmentioning
confidence: 99%